SnO2 Nanoparticle‐Coated ZnO Nanotube Arrays for High‐Performance Electrochemical Sensors. Issue 22 (8th August 2014) - She, Guangwei; Huang, Xing; Jin, Liangliang; Qi, Xiaopeng; Mu, Lixuan; Shi, Wensheng
<x xml:space="preserve">Abstract</x> Novel 1D nanostructures offer new opportunities for improving the performance of electrochemical sensors. In this study, highly ordered 1D nanostructure array electrodes composed of SnO2 nanoparticle‐coated ZnO (SnO2@ZnO) nanotubes are designed and fabricated. The composite nanotube array architecture not only endows the electrochemical electrodes with large surface areas, but also allows electrons to be quickly transferred along the nanotubes. Modifying the SnO2@ZnO nanotube arrays with negatively charged polymer film and employing them as a working electrode, sensitive and selective electrochemical detection of an important neurotransmitter, i.e., dopamine, is realized via the cycle voltammetry (CV) and differential pulse voltammetry (DPV) techniques. Interference from ascorbic acid can be successfully eliminated. The oxidative peak currents recorded from CV linearly depend on the dopamine concentrations from 0.1 to 100 μM with a sensitivity of 2.16 × 10−7 A μM−1 cm−2 and detection limit of 45.2 nM. Using the DPV technique, an improved sensitivity and detection limit of 1.94 × 10−6 A μM−1 cm−2 and 17.7 nM are respectively achieved. Moreover, the SnO2@ZnO nanotube array electrodes can be reused through simple ultrasonical cleaning and no obvious deterioration is observed in the performance.